Are P-glycoprotein (ABCB1/MDR1) and endothelial nitric oxide synthase (eNOS) polymorphisms related to severity of the coronary artery disease? - Öztürk, Ufuk; Gazi, Emine; Özdemir, Öztürk (Journal of Surgery and Medicine, 2022)
Background/Aim: Atherosclerotic cardiovascular disease is one of the most common causes of morbidity and mortality in developed countries. Genetic and environmental factors are associated with atherosclerosis development. Some single nucleotide polymorphisms have also been directly related to atherosclerosis, for example, polymorphisms that reduce nitric oxide (NO) levels and/or activity have been linked to atherosclerotic diseases. However, the multidrug resistance gene 1 (MDR-1) polymorphism is related to repeated cardiovascular events. This study aimed to investigate the relationship between MDR-1 and endothelial NO synthase (e-NOS) polymorphism and severe coronary artery disease (CAD). Methods: In total, 90 patients presenting with acute coronary syndrome were included in this cross-sectional study. Patients with at least > 70% stenosis in ≥ 2 coronary vessels were defined as severe CAD (Group 1), while those with this same level of involvement in < 2 vessels were diagnosed with single-vessel disease (Group 2). MDR 3435C-T and eNOS T-786C were determined by polymerase chain reaction (PCR) amplification. Comparison of parametric and nonparametric values between the two groups was performed using the Student’s t- or Mann–Whitney U test. Categorical variables were analyzed using the χ2 test. Risk estimations for the association of severe CAD with the polymorphisms were calculated using odds ratio (OR) and 95% confidence intervals by comparing the genotypic combinations. Results: Baseline demographic parameters were similar in both groups, except for the presence of DM and glucose level. T allele of MDR was 42% and 40% in groups 1 and 2, respectively (OR = 1.12). The C allele of eNOS was 34% and 30% in groups 1 and 2, respectively (OR = 1.16). Fourteen and 15 patients (40% and 27%, respectively) had both T and C alleles in patients in groups 1 and 2, respectively (OR = 1.77). All P-values were > 0.05. Conclusion: This study is the first one that shows that MDR1 and e-NOS polymorphisms are frequent in patients with ≥ 2 vessel disease and may be associated with severe CAD.